Sexual Harassment in Japanese Politics - Dalton, Emma. author. aut Link
VII, 239 p. 1 illus.
Keywords: "The term sekuhara was popularized in Japan around 30 years ago, but sexual harassment in politics is rarely discussed. This is strange given that longtime legal and social efforts for gender equality have been impeded by politics, an arena that most Japanese consider extremely sexist. Dalton’s striking and persuasive work within the framework of Violence against Women in Politics offers us a clear-cut tool to analyze Japanese politics." -- Yayo Okano, Graduate School of Global Studies, Doshisha University, Japan "Sexual Harassment in Japanese Politics is an insightful examination of the legal, social, and ideological forces that have legitimized the sexual harassment of women in Japanese politics. The book makes a major contribution to the understanding of how sexual harassment and violence against women continue to be tolerated in professional arenas in one of the world’s most gender-unequal countries." -- Kumiko Nemoto, School ofBusiness Administration, Senshu University, Japan Sexual harassment in Japanese politics examines a problem that violates women’s human rights and prevents a flourishing democracy. Japan fares badly in international gender equality indices, especially for female political representation. The scarcity of women in politics reflects the status of women and also exacerbates it. Based on interviews with female politicians around the country from all levels of government, this book sheds light on the sexist and sometimes dangerous environments in Japanese legislative assemblies. These environments reflect and recreate broader sexual inequalities in Japanese society and are a hothouse for sexual harassment. Like many places around the world, workplace sexual harassment laws and regulations in Japan often fail to protect women from being harassed. Even more, in the ‘workplace’ of the legislative council, such regulations are typically absent. This book discusses whatthis means for women in politics in the context of a broader culture whereby victims of sexual violence are largely silenced. Emma Dalton is a Japanese lecturer in the School of Global, Urban and Social Studies at RMIT University.